The Effect of Self-Efficacy and Transformational Leadership on Teacher Performance as an Intervening Variable in State Elementary School - Yunita Fitri Nugraheni; Saiful Anwar; Siti Zubaidah (Mindset : Jurnal Pemikiran Pendidikan dan Pembelajaran, 2025)
This study examined the effects of self-efficacy and transformational leadership on teacher motivation and performance in Public Elementary School Cluster 9, Pamulang Regency. Specifically, it analyzed the direct influence of self-efficacy and transformational leadership on teacher performance, the effect of motivation on performance, and the mediating role of motivation. A quantitative approach with descriptive and associative methods was used, involving 165 teachers selected from a population of 280 using the Slovin formula. Data were analyzed with SPSS. The results indicated that self-efficacy and transformational leadership both had positive and significant direct effects on teacher performance. Teacher motivation also positively influenced performance, confirming its role in supporting teacher effectiveness. Additionally, self-efficacy and transformational leadership positively affected teacher motivation, demonstrating that internal factors and leadership practices contribute to enhancing motivation. Although self-efficacy and transformational leadership indirectly influenced performance through motivation, this mediating effect was smaller than the direct effects, suggesting that motivation partially mediates the relationship. Overall, the findings highlight that self-efficacy and transformational leadership play a dominant role in improving teacher performance, while motivation strengthens performance outcomes. These results emphasize the importance of fostering teacher confidence and effective leadership to enhance educational quality in public elementary schools.